The Impact of a Creative Economy Rooted in Local Cultural Values on Increasing Income - Alana Keylovly; Sara aminah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research explores the impact of the creative economy which is closely related to local cultural values ​​and how this can contribute to increasing income. The main focus of this research is to identify how the creative economy can be rooted in local cultural values ​​and have a positive impact on increasing local community income. The research results show that the integration of local cultural values ​​in the creative economy can create new opportunities for creative economy actors and at the same time have a positive impact on the growth of local community income. In this context, this research provides a deeper understanding of how the creative economy can be a tool for strengthening and preserving local cultural values, while simultaneously improving the economic welfare of society.